Anderson polyoxometalate built-in covalent organic frameworks for enhancing catalytic performances. Issue 17 (21st April 2020) - Ma, Rui; Liu, Naifang; Lin, Ting-Ting; Zhao, Tianbo; Huang, Sheng-Li; Yang, Guo-Yu
Abstract : Anderson polyoxometalate-based covalent organic frameworks exhibited the highest catalytic activity in the photodegradation of RhB and MB, as well as 100% selective oxidation of sulfides to sulfoxides. Abstract : Covalent organic frameworks (COFs) have functional synthons, diverse structures and feature-rich functionality. Herein, the combination of a linear linker NH2 –MMo6 –NH2 with 4-connected tetrahedral tetrakis(4-formylphenyl)silicon building units produced three isostructural complexes M-Anderson-COF s with a 3-fold interpenetrated diamondoid network. Among them, Mn-Anderson-COF exhibited the highest catalytic activity in the photodegradation of RhB and MB in water. The addition of different scavengers demonstrated that 1 O2 and H2 O2 were primary reactive species to degrade the dyes. Moreover, using M-Anderson-COF as a catalyst, organic sulfides were almost completely oxidized with 100% sulfoxide/sulfone selectivity.